Emotional Expressions and Advocacy Coalitions - Allegra H. Fullerton; Kayla M. Gabehart; Christopher M. Weible (International Review of Public Policy)
While many policy process theories mention emotions, they have remained mostly unexplored theoretically and empirically, even as broader social science literature incorporates emotions into understanding policy process-related phenomena such as political beliefs and behaviors. This paper introduces the theoretical arguments and a method for studying advocacy coalitions using a combination of emotions and beliefs within the Advocacy Coalition Framework. An application is illustrated in a natural gas pipeline siting conflict in the US using data from news media coverage. The empirical results show that coalitions express emotions and beliefs differently, and that the dyadic relationship between emotions and beliefs significantly distinguishes coalitions rather than emotions by themselves. This paper takes a significant step forward in integrating emotional and belief expressions into the ACF, adding to coalition identification methods, providing a foundation for advancing theory, and contributing to the broader community of policy studies.